Age and growth of the common guitarfish, Rhinobatos rhinobatos, in Iskenderun Bay (north-eastern Mediterranean, Turkey) - Basusta, Nuri; Demirhan, Sefa Ayhan; Cicek, Erdogan; Basusta, Asiye; Kuleli, Tuncay (Cambridge Univ Press, 2008)
Age and growth of the common guitarfish (Rhinobatos rhinobatos) were estimated from the north-eastern Mediterranean coast of Turkey. A total Of 115 common guitarfish (66 females and 49 males) were sampled. Age determinations were carried out using vertebral sections. Alcian blue dying techniques were used to enhance the visibility of the band on vertebrae. The techniques have been used for the first time on elasmobranchs vertebrae successfully in this study. A total of 97 vertebrae Of 115 were visible on the vertebral band in this study. Male and female common guitarfish ranged in age from 1 to 15 and 1 to 24 y respectively. Total length ranged from 42 to 147 cm for females and 39 to 124 cm for males. The relationships between total length (TL) and total weight (TW) were presented as TW = 0.0014*TL3.1672 (R-2 = 0.98) for females, TW=0.0012*TL3.1947 (R-2 = 0.98) for males and TW=0.0012*TL3.1915 (R-2 = 0.98) for both sexes. The parameters for von Bertalanffy growth curves were estimated as L-inf = 137.70 +/- 9.38 cm, K= 0.159 +/- 0.047, to = -2.180 +/- 0.90 for pooled data.
Keywords: elasmobranchs; Rhinobatos rhinobatos; Iskenderum Bay; age determination; alcian blue dying